A novel colorimetric indicator for ethanol detection in preserved baby mangoes. (1st February 2022) - Kaewnu, Krittapas; Samoson, Kritsada; Thiangchanya, Adul; Phonchai, Apichai; Limbut, Warakorn
Highlights: Smart packaging was designed and fabricated with an ethanol indicator cube. The indicator changed color from yellow to brown, green and blue in 0 to ≥2.5% ethanol. The fabricated indicator cube showed good precision and excellent storage stability. The smart packaging could indicate changing ethanol levels during storage. Abstract: A colorimetric indicator cube for use in smart packaging was designed and fabricated to detect ethanol produced by microbial fermentation in preserved baby mangoes. The presence and level of ethanol was indicated by color variations of the indicator cube, which consists of porous melamine foam (MF) that entraps an indicator solution of potassium dichromate and sulfuric acid. Within the packaging, the cube sits behind a gas-permeable membrane. The morphological structure of MF was studied by digital microscope and X-ray fluorescence analysis. In the optimal condition, the indicator cube exhibited distinct color changes from yellow to brown, green and blue over an ethanol concentration range from 0.25% to 5.0%. Color changes were clearly visible to the naked eye. The repeatability of the ethanol indicator cube was good and storage stability was maintained for up to 19 and 74 days at room and refrigeration temperatures, respectively. The smart packaging was applied to detect ethanol in preserved baby mangoes at different storage times.